Combinatorial discovery of polymers resistant to bacterial attachment - Hook, Andrew L.; Chang, Chien-Yi; Yang, Jing; Luckett, Jeni; Cockayne, Alan; Atkinson, Steve; Mei, Ying; Bayston, Roger; Irvine, Derek J.; Langer, Robert; Anderson, Daniel G.; Williams, Paul; et al. (Nature Publishing Group, 2012)
Bacterial attachment and subsequent biofilm formation are key challenges to the long term performance of many medical devices. Here, a high throughput approach coupled with the analysis of surface structure-property relationships using a chemometics approach has been developed to simultaneously investigate the interaction of bacteria with hundreds of polymeric materials on a microarray format. Using this system, a new group of materials comprising ester and hydrophobic moieties are identified that dramatically reduce the attachment of clinically relevant, pathogenic bacteria (Pseudomonas aeruginosa, Staphylococcus aureus and uropathogenic Escherichia coli). Hit materials coated on silicone catheters resulted in up to a 30 fold reduction in coverage compared to a commercial silver embedded catheter, which has been proven to half the incidence of clinically acquired infection. These polymers represent a new class of materials resistant to bacterial attachment that could not have been predicted from the current understanding of bacteria-surface interactions.